A teoria da dependência enquanto interpretação do desenvolvimento capitalista nas formações sociais periféricas: as versões de Cardoso e Marini - Araujo, Elizeu Serra de (2001)
This work aims to reassess the theory of dependence as an interpretation of capitalist development in peripheral social formations. For that, we take the versions of this theory formulated by Fernando Henrique Cardoso and Ruy Mauro Marini and discuss the scope of their interpretations of Latin American development as representations of a capitalist development process. It seeks to discuss, specifically: the content attributed by the authors to the notion of capitalist development; the place that the development of the capitalist mode of production occupies in its analyzes; and, as a consequence, the extent to which the theoretical instruments constructed by them are appropriate for the investigation of the process of capitalist development in particular peripheral social formations. The work is divided into three chapters: the first two bring the versions mentioned, consisting of an exhibition and a systematization of the main criticisms addressed to them; the third seeks to reassess the reach of these versions from the point of view of its interpretation of capitalist development. The main conclusion reached is that both versions are insufficient in this regard, due to the inadequate treatment they give to the issues of formation and development of the capitalist mode of production in Latin America. It is considered, however, that the dependency theory brought some elements that could be incorporated in a reinterpretation of the capitalist development process in the peripheral social formations, which must necessarily take into account the question of its external insertion.